Articulated System to Analyse Digital Media (ASADM): a proposal about what and how to study online newspapers - Lluís Codina; Rafael Pedraza; Javier Díaz Noci; Ruth Rodríguez-Martínez; Mario Pérez-Montoro; Víctor Cavaller-Reyes (Hipertext.net, 2014)
Throughout this article, we are presenting a proposal to conduct digital media studies as one of the first deliverables of an ongoing research project. This proposal, which we are calling “Articulated System to Analyse Digital Media” (ASADM): consists of a set of concepts presented through specific terminology, and of a group of articulated elements allowing to determine what we call the what (parameters) and how (indicators) of any future study regarding online newspapers or digital media. Thus, we obtain an operative analysis protocol as a deliverable. In between, we characterize the typical context of the sort of studies that constitute the context for our proposal.